2009
DOI: 10.1111/j.1476-5829.2009.00184.x
|View full text |Cite
|
Sign up to set email alerts
|

Canine mammary gland tumours; a histological continuum from benign to malignant; clinical and histopathological evidence*

Abstract: This study describes the clinical and histopathological findings in dogs with mammary gland tumours, and compares the histopathological and clinical evidence consistent with progression from benign to malignant to human breast cancer epidemiology. Clinical and histopathological data on 90 female dogs with 236 tumours was included. Dogs with malignant tumours were significantly older than dogs with benign tumours (9.5 versus 8.5 years), P = 0.009. Malignant tumours were significantly larger than benign tumours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
205
2
29

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(264 citation statements)
references
References 24 publications
28
205
2
29
Order By: Relevance
“…In the present study, the average age was 9.5 years (ranging from 4 to15 years) in dogs with malignant tumours, which was similar to that reported in previous studies (2,27).…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, the average age was 9.5 years (ranging from 4 to15 years) in dogs with malignant tumours, which was similar to that reported in previous studies (2,27).…”
Section: Discussionsupporting
confidence: 80%
“…The dogs ranged from age 2 to 17 years (mean 10 years) and most were of mixed breeds. According to Sorenmo et al (2009) andFerreira et al (2009) models, the staging tests included routine bloodwork (complete blood count, serum chemistry profile), urinalysis, fine needle aspirates of palpable draining lymph nodes, and thoracic radiological examinations. The mammary glands were examined carefully and all tumors were recorded and measured.…”
Section: Specimensmentioning
confidence: 99%
“…Our results indicate that this process also likely occurs in female dogs and that similar studies on the biological behavior of these lesions should be performed in canines. A recent, predominantly epidemiologic report that included clinical and histopathologic data from 90 female canines with 296 tumors hypothesized those malignant mammary tumors could develop from pre-existing low-risk IELs and that the malignant tumors would be the final stage [77]. Although the authors of the report described the very beginning, as also reported for women by Man, et al [20].…”
Section: Discussionmentioning
confidence: 63%
“…The detection of early lesions in MG has demonstrated its importance for preventing and diminishing the mor-that within the same MG there is substantial heterogeneity and that the benign and malignant lesions are multifocal and have variable size, they did not interpret the meaning of these findings. Similarly, Mouser [17] and Sorenmo [77] also reported the multifocality and simultaneous or asynchronous character of IELs and mammary tumors but did not offer any explanations for these changes.…”
Section: Discussionmentioning
confidence: 99%